Efficiency key generation management in a big organization for symmetric cryptography system - Mirzaee, Atefeh (2013)
Nowadays big organizations have complex administrative structure with scattered offices to face with serious problems related to key management like financial and security problems based on symmetric encryption system. This project proposes an efficient solution related to symmetric key crypto system to solve this problem and provide the opportunity for the organization have a secure, affordable, efficient, easier and faster symmetric key crypto system. Symmetric key cryptography with the less key size have more secure in comparison to asymmetric cryptography. Therefore using symmetric key cryptography is more secure and Advantageous. The speed of processing symmetric cryptography is higher than asymmetric cryptography. The purpose of this project is to product the software for all of the employees in the organization to have the secret symmetric key cryptography to have communicatation to each other through the secret key. However, the security of symmetric key cryptography is higher than asymmetric key cryptography. Key derivations algorithm which used in this project is very important for symmetric cryptosystems in comparison with other algorithm because one key can be derived to the others. This Method is chosen by key derivation one-way function and implemented by Delphi programming language. This implemented method give the manager of the organization an opportunity to generate the secret key for all of the employees and so each employee has the symmetric secret key and if the employees need to communicate with each other their request will be sent to the manager. This project has been done in three phases and one of the outcomes of this project is an application which generates random key, according to hierarchy of organization.